Precalculus - Coburn, John W. (Mc Graw-Hill, 2007)
This Precalculus text is written in a friendly and an easy to understand manner in order to help students understand the concept presented. This feature combined with ample examples, various types of exercises, and well thought out, real-world applications give the student the right tools to succeed. There are specific features and exercise problems to incorporate graphing calculator technology for those interested, however the material is presented in a way so that it may be skipped for those not utilizing technology.